Kolloid-chemical and biological characteristics perfluorocarbon emulsion - S. I. Vorobyev; Y. N. Potokin; V. G. Cidorenko; N. V. Gorda (Тонкие химические технологии, 2006)
The article is devoted to physical-chemical and medico-biological characteristics of perfluorocarbon blood substitute perfluoran (PF). The emulsion PF, based upon perfluorocarbon, by no means possesses all the properties of normal blood and does not perform all its functions. However, perfluorocarbon drugs, like PF, can be considered a temporal blood substitute that maintain gas transportation, circulating blood volume, oncotic and osmotic pressure, pH and some other physiological parameters in case of blood loss, surgical operations and organ perfusions. In such cases there is no need to test the blood for compatibility or contamination, what makes it possible to use PF emulsion in extreme and urgent conditions and saves a considerable amount of blood in many areas of medicine, particularly in cases of massive hemorrhage